2000
DOI: 10.1111/j.1532-5415.2000.tb03028.x
|View full text |Cite
|
Sign up to set email alerts
|

Aging‐Related Decline of Gonadal Function in Healthy Men: Correlation with Body Composition and Lipoproteins

Abstract: This study suggests that, in men, androgen decline caused by normal aging does not significantly affect some targets of testosterone action, such as body composition and lipid metabolism. Therefore, androgen supplementation in hypogonadal older men cannot be expected to influence nutritional status and body composition to the same extent that it does other main targets of testosterone action, such as sexual activity and muscle strength. However, we cannot exclude that selected subsets of older patients with lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
2
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 44 publications
1
29
2
1
Order By: Relevance
“…In contrast to these studies, however, Khaw et al (2007) reported that LDL levels were increased in patients in the upper quartile of endogenous testosterone levels compared with the lower quartile, yet a positive association between HDL and testosterone level was apparent. A few cross-sectional studies, however, have found no association between serum lipid measurements and endogenous testosterone (Kiel et al 1989, Denti et al 2000.…”
Section: Testosterone Effects On Lipidsmentioning
confidence: 99%
“…In contrast to these studies, however, Khaw et al (2007) reported that LDL levels were increased in patients in the upper quartile of endogenous testosterone levels compared with the lower quartile, yet a positive association between HDL and testosterone level was apparent. A few cross-sectional studies, however, have found no association between serum lipid measurements and endogenous testosterone (Kiel et al 1989, Denti et al 2000.…”
Section: Testosterone Effects On Lipidsmentioning
confidence: 99%
“…The age trend of serum estrogen in men has been reported variously as declining (8,35) or steady (61). Estrogens were invariant with age in the baseline MMAS (9).…”
Section: Hormone Trendsmentioning
confidence: 99%
“…T and DHEA decline with age, whereas LH, FSH, and sex hormone-binding globulin (SHBG) rise with age (3)(4)(5)(6)(7)(8)(9). At least one important T metabolite, dihydrotestosterone (DHT), apparently remains constant despite the decline of its precursor (9 -12).…”
mentioning
confidence: 99%
“…Por último, la declinación androgénica se acompaña simultáneamente de una caída de estrógenos 3 , la cual está sujeta a las mismas controversias metodológicas del ADAM y cuyo rol biológico es mucho menos claro.…”
Section: Sujetos Y Métodounclassified